The EU ban on uncovered sovereign credit default swaps: assessing impacts on liquidity, volatility and price discovery - Silva, Paulo (2017)
This article addresses the effects of the prohibition against naked CDS buying implemented by the European Union in November 2012. Three aspects of market quality are analyzed: liquidity, volatility, and price informativeness. Overall, our results suggest that the ban produced negative effects on liquidity and price informativeness. First, we find that in territories within the scope of the EU regulation, the bid–ask spreads on sovereign CDS contracts rose after the ban, but fell for countries outside its bounds. Open interest declined for both groups of CDS reference entities in our sample, but significantly more in the constraint group. Price delay increased more prominently for countries affected by the ban, whereas price precision decreased for these countries while increasing for CDSs written on other sovereign reference entities. Most notably, our findings indicate that hese negative effects were more pronounced amid reference entities exhibiting lower credit risk. With respect to volatility, the evidence suggests that the ban was successful in stabilizing the CDS market in that volatility decreased, particularly for contracts written on riskier CDS entities.